Toward a US-Indonesia free trade agreement - Hufbauer, Gary Clyde; Rahardja, Sjamsu, 1969-; Peterson Institute for International Economics (Washington, DC : Peterson Institute for International Economics, 2007)
"Indonesia is the largest Muslim country in the world. Would a free trade agreement (FTA) with the country be both economically and politically beneficial to the United States? What kind of benefits could Indonesia expect? This book presents a case for improved trade relations between Indonesia and the United States and recommends advancing talks toward a US-Indonesia FTA. The authors present a detailed study of the stakes involved in the proposed negotiation and estimate the FTA's potential for trade creation, trade diversion, and welfare under different scenarios."--BOOK JACKET.
1. Introduction -- 2. Natural resources -- 3. Manufactures trade -- 4. Labor and environmental issues in Indonesia -- 5. Government Procurement -- 6. Investment and intellectual property rights -- 7. Services trade -- 8. Estimates from gravity and computable general equilibrium models -- 9. Conclusion -- App. A. technical aspects of the gravity and computable general equilibrium models.
Includes bibliographical references (p. 243-250) and index.
Keywords: United States -- Foreign economic relations -- Indonesia; Indonesia -- Foreign economic relations -- United States